(untitled) (The Journal of Psychology and Sociology, 2019)
In this article there is theoretical analysis and systematization of the concepts of “value” and “value orientation.” It is noted here that the problem of studying the main determinants and the correlation of these concepts for a long time has been the subject of scientific interest of a number of humanitarian disciplines. Nowadays value problems have not lost their relevance, and, what is more, in the context of a changing social reality, it has strengthened its position. As a result it led not only to the need for a deeper understanding of the theoretical foundations of the study of values and value orientations, but also to the search for new methods to study their most important aspects. This article presents several concepts of studying values and value orientations proposed by the leading figures of psychological science - D.А. Leontyev, N.R. Salikhova, A.S. Burelomova, S.L. Rubinstein, B.S. Bratus, L. Lengle, M. Rokich, J. Mussek, Sh. Schwartz. In the concepts they propose the psychological nature of values is explored through the concept of “value orientations of the individual,” which represent systemic education and are a kind of projection into reality, connected not only with values as ideals, but also with a whole range of external and internal conditions. They have a multifaceted structure, which includes such components as social, economic, political, cultural, moral and behavioral aspects. Thus, when a person accepts values that exist in a culture, then they become his personal values. Consequently, value orientations, in turn, express a subjective attitude to one or another value, that is, they reflect the orientation of the individual towards one or another goal.